Field testing of a small-scale anaerobic digester with liquid dairy manure and other organic wastes at an urban dairy farm - Ikko Ihara (2020)
© 2020, Springer Japan KK, part of Springer Nature. Anaerobic digestion has been acknowledged as an appropriate technology to tackle climate change and support sustainable development. In general, biogas installation in developed countries involved a high investment cost due to the size and complexity of the technology, while small and simple technologies are often used in developing countries. In this study, an 8 m3 commercial portable biodigester was modified by installing a mixing device and a heating element coil wire, and fed with liquid dairy manure, dairy by-products and food wastes. The results showed that the mixing device and heating element were effective to keep biodigester temperature around 37.7 °C at an ambient temperature between − 8 and + 25 °C. Higher temperature and longer hydraulic retention time (HRT) were related to higher digestion performance, while the opposite was observed with organic loading rate (OLR). Biodigester performance was not influenced by temperature and HRT, while it was increased with the increase of OLR. The highest biogas yield was observed during the co-digestion of liquid manure with waste milk and food waste, while the highest volumetric production of biogas was observed with liquid dairy manure co-digested with camembert cheese waste and food wastes.